Pneumococcal Sepsis Complicated by Splenic Abscesses and Purpura Fulminans in a 15-Month-Old Child: Case Report and Review of the Literature. (29th February 2016) - Pangonis, Scott; Patamasucon, Pisespong; Fitzpatrick, Ellen
Streptococcus pneumoniae is an invasive organism that causes a wide range of common diseases, including sinusitis, acute otitis media, and pneumonia. Splenic abscesses and purpura fulminans (PF) are rare complications of pneumococcal disease. Splenic abscesses caused by S pneumoniae have only been reported in the adult literature. PF has been described in the pediatric population as a rare complication in patients with invasive pneumococcal disease (IPD) with and without underlying immunological disorders such as asplenia. Here, we report a patient with IPD complicated by splenic abscesses and PF. Our patient initially presented with bacteremia, septic shock, and disseminated intravascular coagulation. She subsequently developed PF and splenic abscesses. She survived her illness after receiving a total of 8 weeks of antibiotic therapy. This case highlights 2 rare complications of IPD and demonstrates the need to keep pneumococcal disease in the differential diagnosis even in children whose vaccination status is up to date.